Use Social Media Knowledge for Exploring the Portuguese Wine Industry - Pérez-Rodríguez, Gael (2022)
This work was supported by the Associate Laboratory for Green Chemistry—LAQV, financed by the Portuguese Foundation for Science and Technology (FCT/MCTES) Ref. UID/QUI/50006/2020; the Portuguese Foundation for Science and Technology (FCT/MCTES) under the scope of Norte2020—Programa Operacional Regional do Norte. Ref. NORTE-01-0145-FEDER-000004; the Consellerıa de Educacion, Universidades e Formacion Profesional (Xunta de Galicia) under the scope of the strategic funding of ED431C2018/55-GRC Competitive Reference Group, the “Centro singular de investigacion de Galicia” (accreditation 2019-2022) funded by the European Regional Development Fund (ERDF)-Ref. ED431G2019/06. Publisher Copyright: © 2022 Gael Pérez-Rodríguez et al.